1989
DOI: 10.1002/anr.1780320105
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic analysis of the distribution of cell adhesion molecules within the inflammatory synovial microenvironment

Abstract: Antigen‐independent binding of T lymphocytes to a variety of cell types has been shown to be mediated by receptor–ligand pairs of adhesion molecules. In forms of inflammatory synovitis (including rheumatoid arthritis), T cells home to synovium, become activated, and participate in the generation of chronic synovitis. Using indirect immunofluorescence assays on synovial frozen tissue sections and on synovial fibroblast cell lines, we studied the distribution of cell adhesion molecules on components of the synov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
72
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(78 citation statements)
references
References 44 publications
5
72
0
Order By: Relevance
“…33, No. 12 (December 1990) been localized in RA synovial tissues and in osteoarthritis synovial tissues by immunocytochemical techniques (8). Our studies extend these initial observations.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…33, No. 12 (December 1990) been localized in RA synovial tissues and in osteoarthritis synovial tissues by immunocytochemical techniques (8). Our studies extend these initial observations.…”
supporting
confidence: 77%
“…It has been demonstrated that the RA synovium contains cells that express HLA-DR antigens (4-7). There is also evidence that indicates that cells populating the inflamed tissue lining the RA joint have adhesion molecules as ligands for homing receptors on circulating T lymphocytes (8,9). It is hypothesized that the increased adhesiveness of the inflamed synovial tissue may play a central role in lymphocyte homing and retention in the diseased joint.…”
mentioning
confidence: 99%
“…However, the possibility that these cells are of synovial origin cannot be excluded as cells of the monocyte/macrophage lineage are found within or lining synovial tissue (Edwards, 1982;Athanasou et al, 1988). Synovial lining cells have an antigen phenotype which closely resembles that of tissue macrophages being characterised by weak or low frequency expression of CD Ila and also CDlIc (Hale et al, 1989;Allen et al, 1989), features not noted in the cases studied.…”
Section: Discussionmentioning
confidence: 79%
“…The synovial microvascular endothelial cell undergoes marked phenotypic alterations in RA, including up-regulation of leukocyte adhesion proteins and immunoreactive COX staining, as well as morphologic alterations in thickness and ultrastructure (17)(18)(19). These changes correlate with well-characterized, cytokine-mediated activation responses of human urn-bilical vein endothelial cells in vitro (20).…”
mentioning
confidence: 99%